Titanium-enriched medium drives low profile of ECM remodeling as a pre-requisite to pre-osteoblast viability and proliferative phenotype - da Costa Fernandes, Celio J. [UNESP]; Bezerra, Fábio J.B. [UNESP]; de Campos Souza, Bruno [UNESP]; Campos, Mônica Aparecida [UNESP]; Zambuzzi, Willian Fernando [UNESP] (Elsevier, 2018)
Titanium is widely used for biomedical applications, but little information is being delivered regarding the cellular/molecular mechanisms explaining their efficacy, mainly considering the effects of the Ti-released trace elements on pre-osteoblasts. We addressed this issue by investigating decisive intracellular signal transduction able to modulate cytoskeleton rearrangement, proliferative phenotype and extracellular matrix (ECM) remodeling. We considered titanium grades IV and V, submitted or not to dual acid-etching (w/DAE or wo/DAE, respectively). Our results showed there is no cytotoxicity, preserving AKT involvement. Additionally, Ti-enriched medium promoted a diminution of the downstream signaling upon integrin activation (phosphorylating Rac1 and cofilin), guaranteeing a dynamic cytoskeleton rearrangement. Moreover, the low profile of ECM remodeling obtained in response to trace molecules released by Ti-based devices seems contributing to the osteoblast performance in mediating extracellular support to cell anchorage. This hypothesis was validated by the up-expression of ß1-integrin, src and Focal adhesion kinase (fak) genes, mainly in response to titanium grade V. Proliferative phenotype showed an unbalance between cyclin-dependent kinases (CDKs) and p15INK4b/p21Cip1. In conjunction, we showed for the first time that trace elements from Ti-based biomedical devices provoke important modulation of the osteoblast biology, driving cell anchoring, viability, and proliferative phenotype. Certainly, these biological outcomes compromise implant osseointegration.
Keywords: Cell adhesion; Cell signalling; Extracellular matrix; Pre-osteoblast; Titanium